Optimizing the Nation's Investment: Persistence and Success in Postsecondary Education - Portch, Stephen R.; Tinto, Vincent; Coles, Amy S.; King, Jacqueline E. (My University, 2002)
Within the context of the forthcoming re-authorization of the Higher Education Act, this conference will focus on how the nation's resources can be best used to optimize student persistence to degree completion. The conference will broaden the discussion about student retention beyond the traditional boundaries that have limited previous debates about persistence. The nation's investment includes federal and state funding, funding for targeted programs by foundations, institutions and other organizations, and the investments made by families and individuals. Nationally distinguished speakers from each of these perspectives will address how the nation's investment can maximize persistence. The program will be convened by Alberto F. Cabrera, Professor, Department of Educational Administration and Senior Scholar, WISCAPE University of Wisconsin-Madison and will include panelists representing national, regional, and state perspectives -- scholars, policymakers, and postsecondary education leaders, along with representatives from public programs and units, private organizations, funding organizations, and accrediting agencies -- who will contribute their extensive knowledge on existing and emerging persistence policy issues.
Keywords: Access, Persistence, and Success